Management consulting - AVAKIAN, Stephanos (Institutional Knowledge at Singapore Management University, 2012)
Including a lengthy, comprehensive introduction, this collection brings together some of the most influential papers that have contributed to our understanding of management consultancy work. The editors have written an original introduction which provides a comprehensive overview of the literature.